Synthesis of The Cu(II)-doped TiO2/Bi2O3 as a Photocatalyst for Rhodamin B Degradation Under Visible Light Ilumination - Aritonang, Anthoni Batahan; Asma, Al; Sapar, Ajuk (BERKALA SAINSTEK, 2023)
The Cu(II)-doped TiO2 and Cu(II)-doped TiO2 /Bi2O3 compound have been synthesized using the sol gel method with titanium tetraisopropoxide (TTIP) as the TiO2 precursor and Cu(NO3)2.3H2O as the Cu(II) dopant was carried out at various concentration of 0.075%; 0.250% and 1.000%, as well as Bi(NO3)3.5H2O as a Bi2O3 precursor. Based on characterization using the DRSUV-Vis spectrophotometric method with data analysis using a tauch plot, it is known that the band gap energy of Cu(II)-doped TiO2 is 2.89 eV; 2.72 eV; 2.54 eV. The addition of Bi2O3 to Cu(II)-doped TiO2 (1%) causes a decrease in the band gap from 2.54 to 2.18 eV which is equivalent to a wavelength of 567 nm. IR spectrophotometry spectra analysis shows a shift in Ti-O absorption towards smaller wave numbers. Characterization by the XRD method shows that 1% Cu(II)-doped TiO2 /Bi2O3 has an anatase phase with a crystallite size of 24 nm. Photocatalysis activity test on the degradation of rhodamine B solution at a concentration of 10 ppm, under visible light illumination for 180 minutes was able to degrade up to 85.85%.